1991
DOI: 10.1111/j.1365-2249.1991.tb02939.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to mouse laminin in patients with systemic sclerosis (scleroderma) recognize galactosyl (αl-3)-galactose epitopes

Abstract: SUMMARYEmploying radioimmunoinhibition assays with distinct oligosaccharides as inhibitors, (his study demonstrates ihat the epitope recognized on mouse laminin by sera from paiients with systemic sclerosis (scleroderma) is a terminal galactosyl (a I -3)-galactose disaccharide. The reaction with this a-digalaetose was further conhrmed when the sera were tested in radioimmunoassay (RIA) binding assay and in ELISA wilh synthetic galactosc al-3 galactose coupled to human serum albumin. The circulating aniibody ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The Gal epitope has also been found on cell associated glycoproteins and glycolipids [23,24], secreted glycoproteins including thyroglobulin, fibrinogen, and immunoglobulin G (IgG) [25,26], and basement membrane proteins such as laminin [27]. Humans and Old World monkeys do not normally express the Gal epitope due to two frameshift mutations in the the α1,3-galactosyl-transferase gene [28,29], and produce large amounts of anti-Gal antibodies (Ab), including IgG, IgM, and IgA [21,[30][31][32][33], as a result of the constant exposure to intestinal bacteria that carry the Gal epitope. It has been estimated that up to 1% of circulating human IgG is anti-Gal [21,31].…”
Section: The Gal Epitopementioning
confidence: 99%
“…The Gal epitope has also been found on cell associated glycoproteins and glycolipids [23,24], secreted glycoproteins including thyroglobulin, fibrinogen, and immunoglobulin G (IgG) [25,26], and basement membrane proteins such as laminin [27]. Humans and Old World monkeys do not normally express the Gal epitope due to two frameshift mutations in the the α1,3-galactosyl-transferase gene [28,29], and produce large amounts of anti-Gal antibodies (Ab), including IgG, IgM, and IgA [21,[30][31][32][33], as a result of the constant exposure to intestinal bacteria that carry the Gal epitope. It has been estimated that up to 1% of circulating human IgG is anti-Gal [21,31].…”
Section: The Gal Epitopementioning
confidence: 99%
“…10,11 Humans and Old World monkeys do not normally express the Gal epitope due to two frameshift mutations in the a 1,3-galactosyltransferase gene, 12,13 but produce large amounts of anti-Gal antibodies (Ab) including immunoglobulin G (IgG), IgM, and IgA. [14][15][16][17][18] Up to 1% of circulating human IgG is anti-Gal. 16,17 Adult human serum typically exhibits an anti-Gal titer of at least 1:800, as measured by rabbit erythrocyte rosetting 16 ; this activity may be equally divided between IgG and IgM.…”
Section: Introduction S M All Intes Tin Al Su B M U C Os a (Sis) Is Amentioning
confidence: 99%
“…When followed over time, only 22% of patients with a variety of inner ear disorders and antilaminin antibodies improved 20 . Studies with sera from patients with Chagas' disease, leishmaniasis, and scleroderma have demonstrated that the circulating antibodies recognize galactosyl (α1‐3)‐galactose epitopes on mouse laminin 25,26 . Anti‐laminin antibodies specific for this mouse epitope were also found in the sera of patients with inner ear diseases 27 .…”
Section: Discussionmentioning
confidence: 99%